The appropriateness of ISDA SIMM for delta risk initial margin calculations in the South African over-the-counter interest rate swap market - Cronje, Robert (Stellenbosch : Stellenbosch University, 2020)
Thesis (MCom)--Stellenbosch University, 2020.